2022
DOI: 10.4103/ija.ija_1076_21
|View full text |Cite
|
Sign up to set email alerts
|

To ascertain the plasma concentration of propofol to achieve bispectral index-guided sedation using a target-controlled infusion in patients undergoing elective surgeries under neuraxial anaesthesia

Abstract: Background and Aims: Sedation improves patient satisfaction, comfort and acceptance of regional anaesthesia. Propofol using bispectral index (BIS)/target-controlled infusion (TCI) system can be an optimal method of sedation, as it combines objective measurement of sedation using BIS along with maintenance of a steady plasma concentration of propofol with the TCI device. The aim of this study was to ascertain the dose and safety of propofol using BIS/TCI system for sedation in patients undergoing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The median recovery time of seven minutes (IQR: 5-10 minutes) and clinical recovery time of seven minutes (IQR: 5-10 minutes) indicate a relatively swift recovery, enhancing the overall efficiency and safety of the sedation protocol. The recovery times align with those of Chhabra et al [ 13 ], who reported a recovery time of 7.39 ± 3.41 minutes while using TCI in patients undergoing surgery under neuraxial block. These findings suggest that the present TCI approach provides effective sedation with rapid onset and recovery, minimizing the duration of patient discomfort and procedural delays.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The median recovery time of seven minutes (IQR: 5-10 minutes) and clinical recovery time of seven minutes (IQR: 5-10 minutes) indicate a relatively swift recovery, enhancing the overall efficiency and safety of the sedation protocol. The recovery times align with those of Chhabra et al [ 13 ], who reported a recovery time of 7.39 ± 3.41 minutes while using TCI in patients undergoing surgery under neuraxial block. These findings suggest that the present TCI approach provides effective sedation with rapid onset and recovery, minimizing the duration of patient discomfort and procedural delays.…”
Section: Discussionsupporting
confidence: 87%
“…The only study that used BIS guidance for titrating the TCI rate is by Chhabra et al, who used it in patients undergoing surgery under neuraxial block. They reported a Cp of 1.13 ± 0.17 µg/ml [ 13 ]. The use of midazolam by Cashion and Treston and neuraxial block by Chhabra et al could have contributed to the lower Cp reported by them as compared to the present study.…”
Section: Discussionmentioning
confidence: 99%